RISK FACTOR STRATIFICATION AND EARLY DETECTION OF INCISIONAL HERNIAS AFTER CESAREAN AND OPEN GYNECOLOGIC PROCEDURES: A PROSPECTIVE OBSERVATIONAL STUDY - Memon, Muhammad M; Salati , Sajad Ahmad; Saadia , Zaheera (Sanamed, 2025)
Background: Incisional hernia is a major complication of abdominal surgery, leading to pain, functional impairment, and increased healthcare costs. This study aimed to identify and rank risk factors for incisional hernia in patients undergoing Cesarean section or open gynecologic surgery, and to evaluate strategies for early detection.Methods: From January 2023 to June 2025, a prospective observational study enrolled 200 women, each followed for 12 months. Half of the women underwent Cesarean section (n=100) and the other half underwent open gynecologic surgery (n=100). Data were collected on patient demographics, body mass index, comorbidities, surgical details, and complications. The primary outcome was the incidence of incisional hernia within one year, assessed by clinical examinations at 6 weeks, 6 months, and 12 months.Results: The overall incidence of incisional hernia was 8.0% (16/200), with 6.0% (6/100) after Cesarean section and 10.0% (10/100) after open gynecologic procedures. Multivariable analysis identified independent risk factors: higher body mass index (adjusted odds ratio 1.12 per unit, 95% confidence interval 1.05–1.19, p
Keywords: Incisional hernia; Cesarean section; gynecologic surgery; risk factors; prospective study; obesity; surgical site infection